Association between dietary intake and physical activity with sleep habits among school-aged children in Kuala Lumpur, Malaysia - Shu Chin Teh; Yeow Nyin Ang; Giin Shang Yeo; Shoo Thien Lee; Kar Hau Chong; Bee Suan Wee; Bee Koon Poh (Discover Public Health)
Abstract Background Despite globally prevalent childhood sleep problems, research on relationships among dietary intake, physical activity, and sleep remains inconclusive. Aim This study aims to investigate these associations among Malay schoolchildren. Methods This cross-sectional study involved 296 Malay schoolchildren aged 9–14 years in Kuala Lumpur, Malaysia. Assessments included a 3-day dietary record, Physical Activity Questionnaire for Older Children (PAQ-C) and Sleep Self-Report (SSR). Results Two in three children (68.2%) did not meet the recommended sleep durations. Boys had significantly higher energy, protein, and carbohydrate intake (p < 0.01) and higher physical activity levels (p < 0.001) than girls. Multiple linear regression showed that age (B = 0.615, 95%CI: 0.315–0.916, p < 0.001) was positively associated with total SSR score, while physical activity (B = −2.139, 95%CI: −3.357 to −0.921, p < 0.01) and energy intake (B = −1.637, 95%CI: −3.093 to −0.181, p < 0.05) were negatively associated. Girls had lower likelihood of experiencing sleep problems (B = −1.492, 95%CI: −2.581 to −0.404, p < 0.01). Protein intake was negatively associated with sleep duration (B = −0.010, 95%CI: −0.020 to 0.000, p < 0.05). Conclusion These findings indicate that dietary intake and physical activity are associated with sleep habits of Malay schoolchildren. Thus, addressing low physical activity and poor dietary habits is essential for interventions aimed at improving children’s sleep habits.